Oxford Handbook of Clinical Haematology, Second edition - Drew Provan, et al. (OXFORD UNIVERSITY PRESS, 2004)
The Concise Oxford Dictionary defines a handbook as ‘a short manual or guide’. Modern haematology is a vast field which involves almost every other medical speciality and which, more than most, straddles the worlds of the basic biomedical sciences and clinical practice. Since the rapidly proliferating numbers of textbooks on this topic are becoming denser and heavier with each new edition, the medical student and young doctor in training are presented with a daunting problem, particularly as they try to put these fields into perspective. And those who try to teach them are not much better placed; on the one hand they are being told to decongest the curriculum, while on the other they are expected to introduce large slices of molecular biology, social science, ethics and communication skills, not to mention a liberal sprinkling of poetry, music and art. In this over-heated educational scene the much maligned ‘handbook’ could well stage a come-back and gain new respectability, particularly in the role of a friendly guide. In the past this genre has often been viewed as having little intellectual standing, of no use to anybody except the panicstricken student who wishes to try to make up for months of mis-spent time in a vain, one-night sitting before their final examination. But given the plethora of rapidly changing information that has to be assimilated, the carefully prepared précis is likely to play an increasingly important role in medical education. Perhaps even that ruination of the decent paragraph and linchpin of the pronouncements of medical bureaucrats, the ‘bulletpoint’, may become acceptable, albeit in small doses, as attempts are made to highlight what is really important in a scientific or clinical field of enormous complexity and not a little uncertainty. In this short account of blood diseases the editors have done an excellent service to medical students, as well as doctors who are not specialists in blood diseases, by summarising in simple terms the major features and approaches to diagnosis and management of most of the blood diseases that they will meet in routine clinical practice or in the tedious examinations that face them. And in condensing this rapidly expanding field they have, remarkably, managed to avoid one of the great difficulties and pitfalls of this type of teaching; in trying to reduce complex issues down to their bare bones, it is all too easy to introduce inaccuracies. One word of warning from a battle-scarred clinician however. A précis of this type suffers from the same problem as a set of multiple-choice questions. Human beings are enormously complex organisms, and sick ones are even more complicated; during a clinical lifetime the self-critical doctor will probably never encounter a ‘typical case’ of anything. Thus the outlines of the diseases that are presented in this book must be used as approximate guides, and no more. But provided they bear this in mind, students will find that it is a very valuable summary of modern haematology; the addition of the Internet sources is a genuine and timely bonus